Detection of Carbapenemase genes in MDR Environmental and Clinical Klebsiella pneumoniae isolates - Mohammed Al-Marjani; Haider Ahmed; Hasan Nimer; Maha Khadim; Sundus Mohammed (Iraqi Journal of Microbiology and Biomedical Science, 2026)
Background: Carbapenem-resistant K. pneumoniae (CRKP) as well as the emergence of other resistance genes such as extended-spectrum beta-lactamases (ESBLs). These bacteria are linked to complicated infection management and contribute to higher morbidity and mortality Objectives: In this study, phenotypic and molecular analyses of multidrug and carbapenem resistance are performed in Klebsiella pneumoniae isolated from clinical and environmental sources in Baghdad, to determine and characterize the prevalence of resistance genes. Methods: A total of 50 clinical isolates were collected from different hospitals and from water sources across various communities; 22 environmental isolates were obtained in Baghdad. The study underscores the extensive occurrence of multidrug-resistant K. pneumoniae in both healthcare and environmental contexts in Baghdad. (56%) and (31.8%) of clinical and environmental carbapenem-resistant Klebsiella pneumoniae isolates, respectively, were metallo-β-lactamase (MBL) producers. Results: Environmental isolates revealed high resistance to ceftazidime (90%) and ampicillin (100%), with blaNDM (17%) and blaOXA-48 (12 %) genes being the most prevalent resistance genes. Carbapenem resistance genes, blaNDM and blaOXA-48 genes, were detected in 19% and 14% of clinical isolates, respectively, whereas the blaIMP gene was not detected. Conclusions: These results highlight the critical importance of strengthening surveillance systems, infection control practices, and antimicrobial stewardship programs to control the spread of resistant K. pneumoniae strains.